Impact of microbial transglutaminase on 3D printing quality of Scomberomorus niphonius surimi. (April 2020) - Dong, Xiuping; Pan, Yuxi; Zhao, Wenyu; Huang, Ying; Qu, Wenhui; Pan, Jinfeng; Qi, Hang; Prakash, Sangeeta
Abstract: In this study, Scomberomorus niphonius surimi was used as the food-ink for 3D printing and microbial transglutaminase (MTGase) as additive, aiming to investigate the effects of MTGase on the forming ability, physical properties and structural qualities of surimi and its 3D printed products. As per the rheological and printing results, the apparent viscosity of surimi containing 0.2% and 0.3% (w/w) MTGase facilitated the extrusion of surimi from the nozzle in time. In addition, the high storage modulus obtained with the two concentrations of enzyme was conductive to the maintenance of shape and appearance after printing of the 3D printed gels. The gel strength reached the maximum value of 2517.89 g mm at 0.3% MTGase concentration, and as the MTGase content increased from 0 to 0.4%, there was a gradual increase in hardness, cohesiveness and resilience of the printed gels. The gel structure changed from irregular distribution to a tight and uniform network that enhanced the ability to restrain residual water, as observed with Nuclear Magnetic Resonance (NMR). On the contrary, cooking loss increased from 4.16% to 13.49%. The results suggest that the use of MTGase can effectively improve the 3D printability, viscoelastic properties, mechanical properties and microstructure of surimi gels. Highlights: 3D printing technology capable of creating a surimi food. Microbial transglutaminase improves the extrudability of surimi. Incorporating microbial transglutaminase impacts surimi 3D printability.